2009
DOI: 10.1163/156854108x398381
|View full text |Cite
|
Sign up to set email alerts
|

Short-term nematode population dynamics as influenced by the quality of exogenous organic matter

Abstract: The food specificity of nematodes, their high number of species and high abundance in every habitat where decomposition takes place, indicate that the structure of the nematode assemblage has a high information content. Since nematodes respond quickly to changes in soil management and since the nematode fauna can be efficiently analysed, the structure of the nematode assemblage offers an interesting instrument to assess changes in soil conditions. We studied the effect of five organic amendments on the shortte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 34 publications
1
16
0
2
Order By: Relevance
“…These data, supported by other studies of agricultural food webs with higher EI , indicated that the available resources were enriched, with higher soil fertility levels, better nutrient availability, etc. ( Ferris et al, 2001; Ferris and Bongers , 2006; Leroy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These data, supported by other studies of agricultural food webs with higher EI , indicated that the available resources were enriched, with higher soil fertility levels, better nutrient availability, etc. ( Ferris et al, 2001; Ferris and Bongers , 2006; Leroy et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Besides higher numbers of active life stages, manured plots also showed higher numbers of dauer juveniles, a dormant stage of bacterialfeeding nematodes. Similarly, those manured plots often also showed higher numbers of omnivorous nematodes (van Diepeningen et al, 2006;Birkhofer et al, 2008;Hu & Cao, 2008;Leroy et al, 2009;Hu & Qi, 2010a, b), while numbers of carnivorous nematodes were unaffected.…”
Section: Carnivorous Nematodesmentioning
confidence: 97%
“…The relative abundance of different species of collembola, however, was more negatively affected by application of cattle slurry. Similar increased biomass or numbers in response to manure applications have been observed for protozoa (Griffiths et al 1998), nematodes (Opperman et al 1993;Griffiths et al 1998;De Goede et al 2003;Birkhofer et al 2008;Leroy et al 2009;van Eekeren et al 2009), and various arthropods (Pfiffner and Niggli 1996). Overall, the responses of soil fauna and community interactions in soil are complex and may be related to differences in excreta types, soil properties, and management systems.…”
Section: Animal Manuresmentioning
confidence: 59%